Python for Unix and Linux system administration - Gift, Noah (O'Reilly Media, 2008)
"Python for Unix and Linux System Administration demonstrates how the Python language offers you a more efficient way to handle various tasks when managing Unix and Linux servers. Each chapter presents a particular administrative issue, such as concurrency or data backup, and offers Python solutions through hands-on examples. You'll learn to develop your own set of command-line utilities with Python to tackle a wide range of problems."--Jacket